Factors influencing the accuracy of intraoral scanning (Research, Society and Development, 2025)
This review aimed to identify available studies that reported the factors influencing the accuracy of digital dental impressions. Searches were carried out for articles in Portuguese and English. in databases PubMed, Scielo, Lilacs, and Google Scholar, with the descriptors “digital dentistry, precision, intraoral scanner, digital impression, scanning”, published between the years 2006 and 2024. 41 articles were found and after reading the title and abstract, only 28 were used for this review. The review found that intraoral scanners present inherent distortions, due to optical and software imperfections. Key factors that affect scanning accuracy include operator experience, scanning time, scanner type, and scan size. More experienced operators and smaller scan sizes provided more accurate scans. It was concluded that adequate training and appropriate choice of equipment are essential to optimize clinical results, emphasizing the importance of these factors in obtaining accurate fingerprints.